(untitled) (Transport systems and technologies, 2018)
The reform of the railway industry of Ukraine leads to changes in the organization of contract work in the model "Customer-Railway". The customers of railways service constantly set the tasks before the management of the railway that needed to be resolved. For example it was necessary to improve the interaction of the railways activity and users of its services. The proposed Ukrainian Railways PJSC scheme for 2018 provides for an automated and paper-based registration of contracts through the Center for Transport Logistics(CTL), which simplifies the procedure for concluding contracts and makes it possible to make settlements for transportation through the Unified Settlement Center (USC). The distinct feature of the new contract for providing the services related to the organization of goods transportation in domestic and international communications is the definition of the identity of railway carriage (container) of the carrier. Thus only the introduction of a new contract without capital investment and the introduction of technical means increased transportation charges that are the significant expense for railroad users and increase immensely the cost of goods. For efficient use of the carriages of the carrier, it is necessary to determine the standard number of days of the carriage in the freight and empty runs. Such a prospect as the creation of a powerful carrier UZ Cargo, which will dictate the conditions in the transportation market, will improve the efficiency of the use of railroad rolling stock, increase profits and assignations for infrastructure modernization.